Analisis Faktor Yang Berhubungan Kejadian Preeklamsi Pada Ibu Hamil Di Di Klinik Pratama Murni Sibuluan Tahun 2025 - Jenni Susi Sihite (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Preeclampcia is cummulative symtom arising at pregnant mother and maternity which trias symtom: hipertension, proteinuria with and without oedema. But most of women do not have enough knowledge about the symtoms. Consequently, it is always too late to take necessary measure resulting other complication. Because of that, preeclmpcia is one of the main couse of womens death. The aims of this research is to identify the risk of preeclampcia on pregnant women pure primary clinic sibuluan. This reseach use cross sectional design. The population is all of pregnant woment with preeclampcia, twenty four sample were taken by cosecutive sampling. Independent variable in this research are age, parity, individual history disease, family history, antenatal care history, weight gain, and family income. Dependen variable is pregnant woment with preeclampcia. Data was analyzed using chi square with the significance p≤0,05. The result show there is corelation betwen preeclampcia with age (p=0,019) and individu history disease (p=0,013). While the factors parity (p=0,525), family disease history (p=0,558), antenatal care history (p=0,602), weight gain (p=646), and family income (p=0,206) doesn’t have correlation with preeclamcia case. For that the pregnant women who already identify for more do antenatal care so thet progress can be monitoted. For the health workers expected to take care fort hose people who identified the risk of preeclampcia.